2015
DOI: 10.1044/2014_lshss-14-0045
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Co-Occurring Attention-Deficit/Hyperactivity Disorder on Children's Language Impairments

Abstract: Purpose Co-occurring attention-deficit/hyperactivity disorder (ADHD) and communication disorders represent a frequently encountered challenge for school-based practitioners. The purpose of the present study was to examine in more detail the clinical phenomenology of co-occurring ADHD and language impairments (LIs). Method Measures of nonword repetition, sentence recall, and tense marking were collected from 57 seven- to nine-year-old children. The performances of children with ADHD+LI status were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Information on this question is limited. Redmond, Ash, and Hogan (2015) administered measures of tense marking, nonword repetition, and sentence recall to children with SLI, ADHD+LI, and TD. The results indicated that performance levels associated with the SLI and ADHD+LI groups were very similar, indicating that ADHD had no independent detrimental impact on children's LI.…”
Section: Impact Of Co-occurring Adhd On LImentioning
confidence: 99%
“…Information on this question is limited. Redmond, Ash, and Hogan (2015) administered measures of tense marking, nonword repetition, and sentence recall to children with SLI, ADHD+LI, and TD. The results indicated that performance levels associated with the SLI and ADHD+LI groups were very similar, indicating that ADHD had no independent detrimental impact on children's LI.…”
Section: Impact Of Co-occurring Adhd On LImentioning
confidence: 99%
“…For instance, demonstration that ADHD+LI < SLI in performance on either tense marking, nonword repetition, or sentence recall would provide support to the premise that components of information processing that have been implicated in ADHD represent potential causal contributors to children's language impairments. Redmond, Ash, and Hogan (2015) compared the performances of children with ADHD+LI on tense marking, nonword repetition and sentence recall to those of a matched group of children with SLI and those of children with TD. Data for some of the participants in the SLI and TD group were taken from the Redmond et al (2011) study sample.…”
Section: The Impact Of Co-occurrence On Symptom Presentationmentioning
confidence: 99%
“…Although attention is related to working memory, the correlations for both ratings scales and objective tests with working memory are typically moderate (e.g., Swanson, 2011 ). In relation to attention and comprehension, several studies have demonstrated a relation between ADHD and poor reading and listening comprehension (Brock & Knapp, 1996 ; Martinussen & Mackenzie, 2015 ; McInnes, Humphries, Hogg-Johnson, & Tannock, 2003 ; Redmond, Ash, & Hogan, 2015 ). This is most likely due to children with ADHD having fewer cognitive resources to allocate to the integration of ideas within a text and the construction of the mental model, evidenced by poorer recall of the central ideas in a text (Miller et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%